Al-Idhâfah Fî Al-Lughah Al-‘Arabiyah Wa Al-Lughah Al-Indûnîsiyah Dirâsatan Taqabuliyyatan - Juliana Podungge; Nofa Isman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
هدفت هذه الدراسة إلى معرفة بين الإضافة في اللغة العربية واللغة الإندونيسية لاكتشاف أوجه التشابه والإختلاف بينهما من الناحية الصرفية، والنحوية، والدلالية تسهيلا لتنبؤبالصعوبات التي يتوقع حدوثها أن يوجهها الدارسين الإندونيسيين أثناء التعلم ثم يرجى أن تكون هذه الدراسة الحصول على إعداد المواد الدراسية لتعليم اللغة اللغة العربية لدى المبتدئين الإندونيسيين على مستوى الإضافة. نهجت هذه الدراسة المنهج الوصف التحليلي للوقوف على خصائص الإضافة في اللغتين؛ العربية والإندونيسية، والمنهج التحليل التقابلي لمقارنة الأنظمة في اللغتين. واستنتجت من هذه الدراسة أن توجد أوجه التشابه والاختلاف بين الإضافة في اللغة العربية واللغة الإندونيسية من الناحية الصرفية والنحوية والدلالية. This study is aimed t know the phrase between the Arabic languange and Indonesian languange in order to determine the similarities and differences among them in terms of morphology, syntax, and semantic, it is to expected to predict the difficulties that will be faced by Indonesian students during the teaching activities, and then it is expected to porpose a method of teaching based on the result of the contrastive study to teach Arabic languange at the level of the phrase for beginner students og Indonesian. This study uses methodology of descriptive analysis to identify the characteristics of phrase in Arabic and Indonesian, and then using the method of comparative analysis to compare Arabic and Indonesian languange at the level of phrase in order to obtain the similarities and differences between these both languange. The result of this research is there are similarities and differences of phrase in Arabic and Indonesian in terms of morphology, syntax, and semantics.